Beschäftigungsentwicklung in Mitteldeutschland: Sachsen-Anhalt und Thüringen im Vergleich - Farhauer, Oliver; Granato, Nadia (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Comparing the labour market situation in East Germany shows that the employment volume in Sachsen-Anhalt has considerably declined whereas Thüringen has been performing much better. In our paper we analyse indicators relevant to employment development in both federal states (Bundesländer) using a benchmark approach. This reveals, that Thüringen is better equipped with regard to all indicators, the most pronounced differences being related to location factors and industry structure.